TEACHERS’ PERCEPTION ON THE INSERTION OF BALINESE CULTURE IN BIPA INSTRUCTION - Sudana, Putu Ayu Prabawati; Utama, I Dewa Gede Budi; Paramarta, I Made Suta; Paragae, IGA Pt. Novita Sari (Lingua Scientia, 2021)
The aims of this research were analyzing teachers’ perception on the insertion of Balinese culture in BIPA instruction and the ways to present culture in the instruction. This study used descriptive qualitative method. The data were collected by using questionnaire distributed to BIPA teachers in Undiksha Language Center and through interview as well as focused group discussion. The data were analysed quantitatively by looking at the percentage of response given by teachers and qualitatively by using the method of data analysis consisting of data reduction, data display and conclusion drawing. The result of the study showed that BIPA teachers support the insertion of Balinese culture in the instruction. In addition, there were found several ways to present the culture in the instruction, namely (1) presenting culture boxes in the textbook, (2) using authentic materials, (3) supporting the students to interact with native speakers and (4) presenting cultural elements through reading text and listening activities.Keywords : Balinese Culture, BIPA, Instruction